FUNCTIONYMS AND THEIR INTERRELATIONS WITH THE MACROSTRUCTURE OF VOCABULARY (Scientific journal of the Fergana State University, 2023)
The article discusses the relationship of functionyms that relate to the mediostructure of the dictionary and the phenomena of the lexical-thematic group and the lexical-semantic field, which were the main types of the macrostructure of the vocabulary.